Monitoring loads and non-contact injury during the transition from club to National team prior to an international football tournament: A case study of the 2014 FIFA World Cup and 2015 Asia Cup. Issue 8 (August 2018) - McCall, Alan; Jones, Mark; Gelis, Les; Duncan, Craig; Ehrmann, Fabian; Dupont, Gregory; Duffield, Rob
Abstract: Objectives: Injured and non-injured national team footballers were compared for external and internal loads during transition from club to National team training camp. Design: Prospective Case Study. Methods: Load and injury data were collected from the same National team prior to and during training camps of 2 tournaments; World (n = 17) and Asian Cups (n = 16). External (number sessions) and internal (s-RPE) loads were collected 4-weeks prior to and during camps. The acute:chronic load ratio was calculated for the first week of camp based on the mean of previous 4-weeks. Respective loads and ratios were compared between injured and non-injured players for non-contact injuries occurring during camp. Results: Seven non-contact injuries occurred during World Cup camp and 1 during Asian Cup (preventing statistical analyses). Small-to-moderate effect sizes were found for lower chronic internal loads (ES = 0.57; 90% CI: 0.39–1.08) and higher acute:chronic ratio (ES = 0.45; 90% CI: 0.31–0.87) for injured compared to non-injured players. Moderate-large effects (ES = 0.83; 90% CI: 0.56–1.60) were evident for increased acute:chronic ratio for number of sessions in injured compared to non-injured players. However, small-moderate effect sizes were present for lower chronic training and match loads (ES = 0.55; 90% CI: 0.38–1.06) in injured players prior to the World Cup camp, alongside an increased number of sessions in week 1 of camp (ES = 0.47; 90% CI: 0.33–0.91). Conclusions: Players incurring non-contact injury during training camp prior to an international tournament performed less prior chronic external and internal load and a concomitant higher relative increase in camp, thus representing a practical marker to monitor in national teams.